2010
DOI: 10.1007/s11340-010-9359-x
|View full text |Cite
|
Sign up to set email alerts
|

In situ Study of Cracking and Buckling of Chromium Films on PET Substrates

Abstract: Chromium (Cr) films are widely used as interlayers to promote the adhesion of copper or gold to substrates. However, the Cr interlayer usually fractures at lower strains than the ductile metal films. In this paper, the cracking and buckling behavior of Cr films on polyethylene terephthalate (PET) substrates were studied in situ under tensile loading with the Atomic Force Microscope (AFM) and optical microscope imaging. Cr films with three nominal thicknesses of 15, 70 and 140 nm were studied. The depth and wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Additionally, the CuTi film was strained in situ under the atomic force microscope (AFM) [25,30–33] to better observe the surface deformation (necking) and crack formation as a function of strain. For this, a miniaturized screw-driven tensile stage was utilized with a 25 μm × 25 μm scan size at 1 Hz and a 512 dpi resolution.…”
Section: Materials/experimentalmentioning
confidence: 99%
“…Additionally, the CuTi film was strained in situ under the atomic force microscope (AFM) [25,30–33] to better observe the surface deformation (necking) and crack formation as a function of strain. For this, a miniaturized screw-driven tensile stage was utilized with a 25 μm × 25 μm scan size at 1 Hz and a 512 dpi resolution.…”
Section: Materials/experimentalmentioning
confidence: 99%
“…Samples were strained to crack and buckle saturation at room temperature in the MD. Other studies of Cr films on compliant substrates have observed similar channel cracking and buckles forming between cracks [6,10,29,30]. The evolution of the crack density (1/) with ex situ straining is shown in Figure 5 for the 15-and 150-nm Cr films strained at 4 Â 10 À4 s À1 on PET substrates in the MD Crack spacings at saturation are also the same in both orientations for the 150-nm film: ¼ 9.5 AE 3.2 mm in the MD and ¼ 9.1 AE 1.3 mm in the TD.…”
Section: Effect Of Substrate Thickness and Orientation On Film Behaviourmentioning
confidence: 74%
“…3(b), where one can see that the average buckle heights and widths generally increased with increasing the modulation period λ . Jin et al [22] found that, in the single layer Cr films on flexible polyethylene terephthalate substrate, both the buckle widths and heights markedly increased when the film thickness was varied from 15 nm to 140 nm. Similar results were observed in Pundt et al's work [17,23] on polymer-supported Nb films.…”
Section: (A)mentioning
confidence: 99%